Impact of SARS-CoV-2 vaccination on FcγRIIIA/CD16 dynamics in Natural Killer cells: relevance for antibody-dependent functions - Capuano, Cristina; De Federicis, Davide; Ciuti, Daniel; Turriziani, Ombretta; Angeloni, Antonio; Anastasi, Emanuela; Giannini, Giuseppe; Belardinilli, Francesca; Molfetta, Rosa; Alvaro, Domenico; Palmieri, Gabriella; Galandrini, Ricciarda (Frontiers in Immunology, 2023)
Introduction: Natural Killer (NK) cells contribute to the protective effects of vaccine-induced antibodies thanks to the low affinity receptor for IgG, FcγRIIIA, CD16, whose aggregation leads to the killing of infected cells and IFNγ release, through which they potentiate adaptive immune responses. Methods: Forty-seven healthy young individuals undergoing either homologous (ChAdOx1-S/ChAdOx1-S) or heterologous (ChAdOx1-S/BNT162B2) SARS-CoV-2 vaccination settings were recruited. Peripheral blood samples were collected immediately prior to vaccination and 8 weeks after the booster dose. The phenotypic and functional profile of NK cells was evaluated by flow cytometry at both time points. Serum samples were tested to evaluate circulating anti-Spike IgG levels and cytomegalovirus serostatus. CD16 F158V polymorphism was assessed by sequencing analysis. Results: The downregulation of CD16 and the selective impairment of antibody-dependent cytotoxicity and IFNγproduction in CD56dim NK population, persisting 8 weeks after boosting, were observed in heterologous, but not in homologous SARS-CoV-2 vaccination scheme. While the magnitude of CD16-dependent functions of the global CD56dim pool correlated with receptor levels before and after vaccination, the responsivity of NKG2C+ subset, that displays amplified size and functionality in HCMV+ individuals, resulted intrinsically insensitive to CD16 levels. Individual CD16 responsiveness was also affected by CD16F158V polymorphism; F/F low affinity individuals, characterized by reduced CD16 levels and functions independently of vaccination, did not show post-vaccinal functional impairment with respect to intermediate and high affinity ones, despite a comparable CD16 downregulation. Further, CD16 high affinity ligation conditions by means of afucosylated mAb overcame vaccine-induced and genotype-dependent functional defects. Finally, the preservation of CD16 expression directly correlated with anti-Spike IgG titer, hinting that the individual magnitude of receptor-dependent functions may contribute to the amplification of the vaccinal response. Conclusions: This study demonstrates a durable downmodulation of CD16 levels and Ab-dependent NK functions after SARS-CoV-2 heterologous vaccination, and highlights the impact of genetic and environmental host-related factors in modulating NK cell susceptibility to post-vaccinal Fc-dependent functional impairment.